Antimicrobial activity of Sindora bruggemanii (sepetir) oil / Muhd Nor Hazli Nordin - Nordin, Muhd Nor Hazli (2005)
It is recognized that poor hand washing compliance is a key factor in the spread of infections in the healthcare environment. Even with the introduction of new and improved formulations of hand washes, many have rejected its use as high frequency, repeated hand washing can damage skin thus leading to irritant contact dermatitis or other skin-related problems. Natural plant extracts or oil with antimicrobial property may be incorporated to produce a mild and moisturizing yet effective hand wash. In the present study, a novel oil from Sindora bruggemanii, known as sepetir, which is used among the locals for wound healing was assessed for its potential as an antimicrobial agent to be incorporated in hand washes. The secondary objective was to assess the efficacy of a commercial preparation of tea tree oil, and water- and oil-base sea cucumber (‘gamat’) preparations against E. coli (ATCC 25922), S. aureus (ATCC 6538), M. luteus (ATCC 10240), and C. albicans (ATCC 10231). The antimicrobial activity of two commercial hand washes (water-base hand wash, Dettol and alcohol-base hand wash, Aubry) were also evaluated. A revised method of agar-well diffusion technique was adapted and all compounds were tested against human pathogens. The efficacy of each compound was determined by the inhibition zone produced. Sepetir oil was able to provide a significant (P<0.05) inhibition but only limited to Gram positive bacteria. Tea tree oil exhibited a strong antibacterial and antifungal activity against all pathogens studied, yielding a significantly (P<0.01) large inhibition zone. Both the commercial preparations of sea cucumber had no inhibitory effect on any of the above-mentioned microorganisms. Water-base hand wash (Dettol) on the other hand, provided broad and significant (P<0.05) protection against these microorganisms compared to alcohol-base hand wash (Aubry). Results indicate that tea tree oil is more promising than sepetir oil to be used as a component of hand washes in future.